2010
DOI: 10.1557/jmr.2010.0180
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale phase transitions under extreme conditions within an ion track

Abstract: The dynamics of track development due to the passage of relativistic heavy ions through solids is a long-standing issue relevant to nuclear materials, age dating of minerals, space exploration, and nanoscale fabrication of novel devices. We have integrated experimental and simulation approaches to investigate nanoscale phase transitions under the extreme conditions created within single tracks of relativistic ions in Gd2O3(TiO2)x and Gd2Zr2–xTixO7. Track size and internal structure depend on energy density dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
101
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 42 publications
15
101
0
4
Order By: Relevance
“…A variety of criteria have been proposed as predictors of radiation tolerance, including bond covalency 5 , susceptibility to disordering 2 , thermodynamic stability 6 and grain size 7 . However, relating trends in radiation tolerance to the dynamic process of radiation damage accumulation is difficult due to the complex nature of defect production and recovery, both of which occur at nanometric length scales, femto-and picosecond timescales, and extremely high energy densities 8 . In addition, the conditions under which a material is irradiated can drastically affect its response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of criteria have been proposed as predictors of radiation tolerance, including bond covalency 5 , susceptibility to disordering 2 , thermodynamic stability 6 and grain size 7 . However, relating trends in radiation tolerance to the dynamic process of radiation damage accumulation is difficult due to the complex nature of defect production and recovery, both of which occur at nanometric length scales, femto-and picosecond timescales, and extremely high energy densities 8 . In addition, the conditions under which a material is irradiated can drastically affect its response.…”
mentioning
confidence: 99%
“…Electronic stopping results in extensive local ionization, yielding excitation densities of up to several keV nm À 3 within a nanometric cylinder along the ion trajectory 15 . Although the atomistic modifications that occur following this electron cascade have been extensively studied 8,13 , the relaxation of these delocalized electrons is complex and difficult to relate directly to atomic behaviour 16 . It is generally assumed that electron-hole recombination leads to recovery of the pre-irradiation charge distribution 13 but, given the highly nonequilibrium conditions under which relaxation of the electron cascade occurs, electronic structure modifications are possible.…”
mentioning
confidence: 99%
“…Due to its radiation tolerance, pyrochlores are seen as a candidate for application such as inert matrix fuels, nuclear waste immobilization and geological age-dating. [1,2] However, radiation under such extreme conditions introduces phase transformation in the ordered pyrochlore structure, which is critical to understand for such applications. High energy ion irradiation (MeV to GeV) on pyrochlores is seen as an important experiment to understand the phase transformations which take place due to localized (nanoscale) energy transfer to the lattice in extremely short time period (~ns).…”
mentioning
confidence: 99%
“…Crocombette [74] has compared defect production by displacement cascades and thermal spikes and concluded that while the number of defects produced in simulations of cascades and spikes can be different, the overall characteristics of the damage are quite similar. Recently, Zhang et al [75] showed that thermal spike simulations can reproduce the microstructural features of ion tracks and the amorphization tendency observed in experimental irradiation of pyrochlore compounds. These findings suggest that thermal spike simulations can be used to quickly screen candidate waste forms based on their tendency to undergo direct-impact amorphization.…”
Section: Modeling Of Ceramic Waste Formsmentioning
confidence: 99%